58.7k views
3 votes
Explain how the Distributive Property can be used to expand the expression on the left side of the equation.

3(x + 4) = 36.

A.
Add 3 to each term inside the parentheses.


B.
Subtract 3 from each term inside the parentheses.


C.
Multiply each term inside the parentheses by 3.


D.
Divide both terms inside the parentheses by 3.

2 Answers

2 votes

Answer:

C.

Multiply each term inside the parentheses by 3.

Explanation:

User Leszek Jasek
by
5.6k points
2 votes

Answer:

C. Multiply each term inside the parentheses by 3.

Explanation:

The distributive property lets you multiply a sum by multiplying each addend separately and then add the product.

The stated distributive property shows that option C. is correct

C. Multiply each term inside the parentheses by 3.

To confirm the claim of this option, let's multiply each term inside the parentheses by 3.

Term: 3(x + 4) = 36

Multiply: 3*x + 3 * 4 = 36

=> 3x + 12 = 36

Collect like terms

3x = 36 - 12

3x = 24

Divide through by 3

3x/3 = 24/3

x = 24/3

x = 8

Hence, it's shown that to solve this expression, we have to multiply each term inside the parentheses by 3.

User Biks
by
5.7k points